Synthesis and characterization of metallo phthalocyanines bearing 7-oxy-3-(4-pyridyl)coumarin substituents and their supramolecular structures with vanadyl bis(acetylacetonate) - KARACA ALBAYRAK, FATMA (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
The synthesis of novel zinc and cobalt metallo phthalocyanines with four 7-oxy-3-(4-pyridyl)coumarin dye groups on the periphery/non-periphery were prepared by cyclotetramerization of 7-(3,4-dicyanophenoxy)-3-(4-pyridyl)coumarin (1)/7-(2,3-dicyanophenoxy)-3-(4-pyridyl)coumarin (2) and also a phthalocyanine based on supramolecular structures have been prepared by the ready coordination of pyridine donor sites in 2,9(10),16(17),23(24)-tetrakis[7-oxo-3-(4-pyridyl)coumarin]-phthalocyaninatozinc (1a)/1,8(11),15(18),22(25)-tetrakis[7-oxo-3-(4-pyridyl)coumarin]-phthalocyaninatozinc (2a) with vanadyl bis(acetylacetonate). The novel chromogenic compounds were characterized by elemental analysis, H-1 NMR, Mass spectra, FT-IR and UV-Vis spectral data. The IR-spectra of prepared compounds showed two characteristic intense bands at 1728-1719 cm(-1) for lactone carbonyl and at 1592 cm(-1) for the alpha, beta unsaturated doubled bond. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Coumarin (2H-1-benzopyran-2-one); Cobalt; Phthalocyanines; Vanadyl bis(acetylacetonate); Zinc; ELECTROCHEMICAL PROPERTIES; ZINC PHTHALOCYANINES; THIN-FILMS; COUMARIN; DERIVATIVES; COMPLEXES; MACROCYCLES; MOIETIES; COBALT; ACIDS